Estrogen or antiprogestin treatment induces complete regression of pulmonary and axillary metastases in an experimental model of breast cancer progression - Vanzulli, Silvia (2005)
In this paper we demonstrate, using the C7-2-HI metastatic transplantable ductal mammary tumor, that endocrine therapy can induce complete regression of spontaneous lymph node and lung metastases in a mouse model of breast cancer progression. This tumor expresses high levels of estrogen and progesterone receptors and shows a high incidence of early axillary lymph nodes and lung metastases; using this model we had previously shown complete tumor regression of subcutaneous implants. Interestingly, although the metastases showed a more differentiated histology as compared with the primary growth, they underwent complete regression when treated with estrogens or antiprogestins. This phenomenon was associated with sustained cytostasis and apoptosis accompanied by increases in p21 and p27 expression and early tissue remodeling. These results highlight the essential role of PR in regulating cell proliferation in this model as well as its possible use as therapeutic target.